Comprehensive Analysis Identifies THEMIS2 as a Potential Prognostic and Immunological Biomarker in Glioblastoma - Jianan Chen; Qiong Wu; Anders E. Berglund; Robert J. Macaulay; Arnold B. Etame (Cells)
Glioblastoma (GBM) is a highly aggressive brain tumor characterized by its ability to evade the immune system, hindering the efficacy of current immunotherapies. Recent research has highlighted the important role of immunosuppressive macrophages in the tumor microenvironment (TME) in driving this immune evasion. In this study, we are the first to identify THEMIS2 as a key regulator of tumor-associated macrophage (TAM)-mediated immunosuppression in GBM. We found that a high THEMIS2 expression is associated with poor patient outcomes and increased infiltration of immune cells, particularly macrophages. Functional analyses revealed THEMIS2’s critical involvement in immune-related pathways, including immune response activation, mononuclear cell differentiation, and the positive regulation of cytokine production. Additionally, single-cell RNA sequencing data demonstrated that macrophages with a high THEMIS2 expression were associated with increased phagocytosis, immune suppression, and enhanced tumor growth. These findings suggest that THEMIS2 could serve as both a prognostic marker and a therapeutic target for enhancing anti-tumor immunity in GBM.